Role of Egr1 on Pancreatic Endoderm Differentiation - Tsugata, Takako (Cell Med, 2018)
The low efficiency of in vitro differentiation of human embryonic stem cells (hESCs) or human-induced pluripotent stem cells (iPSCs) into insulin-producing cells is a crucial hurdle for the clinical implementation of human pluripotent stem cells (PSCs). Our previous investigation into the key factors for the differentiation of PSCs into insulin-producing cells suggested that the expression of GATA binding protein 6 (GATA6) and Gremlin 1 (GREM1) and inhibition of early growth response protein 1 (Egr1) may be important factors. In this study, we investigated the role of Egr1 in pancreas development. The transfection of small interfering RNA (siRNA) of Egr1 in the early phase induced the differentiation of iPSCs derived from fibroblasts (FiPSCs) into pancreatic endoderm and insulin-producing cells. In contrast, the downregulation of Egr1 in the late phase suppressed the differentiation of FiPSCs into pancreatic endoderm and insulin-producing cells. In addition, the overexpression of Egr1 suppressed the differentiation of iPSCs derived from pancreatic cells into pancreatic endoderm and insulin-producing cells. These data suggest that the downregulation of Egr1 in the early phase can efficiently induce the differentiation of iPSCs into insulin-producing cells.